2008
DOI: 10.1017/s1368980007001449
|View full text |Cite
|
Sign up to set email alerts
|

WHO 2006 child growth standards: implications for the prevalence of stunting and underweight-for-age in a birth cohort of Gabonese children in comparison to the Centers for Disease Control and Prevention 2000 growth charts and the National Center for Health Statistics 1978 growth references

Abstract: Objectives: To assess the proportion of children being stunted and underweightfor-age at 3, 9 and 15 months in Lambaréné, Gabon, using the WHO child growth standards released in 2006 as compared with the Centers for Disease Control and Prevention (CDC) 2000 and the National Center for Health Statistics (NCHS) 1978 child growth charts/references. Design and setting: Prospective birth cohort in Lambaréné, Gabon. Subjects: Two hundred and eighty-nine children from birth to 15 months of age. Methods: Weight and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 26 publications
5
30
2
Order By: Relevance
“…Difference between the WHO and USCDC height-for-age z score means and estimates for stunting by the WHO and USCDC references was not significant. Previous studies reported a lower prevalence of underweight and stunting while a higher prevalence of overweight and obesity using the WHO reference compared to the USCDC reference [39-42]. The USCDC growth charts over-estimate the under-nutrition and under-estimate the over-nutrition.…”
Section: Discussionmentioning
confidence: 97%
“…Difference between the WHO and USCDC height-for-age z score means and estimates for stunting by the WHO and USCDC references was not significant. Previous studies reported a lower prevalence of underweight and stunting while a higher prevalence of overweight and obesity using the WHO reference compared to the USCDC reference [39-42]. The USCDC growth charts over-estimate the under-nutrition and under-estimate the over-nutrition.…”
Section: Discussionmentioning
confidence: 97%
“…To date, a number of studies have examined the impact of the implications of the WHO growth standards on growth assessment or specific nutrition-related outcomes, such as obesity, in other countries (18)(19)(20)(21)(22)(23)(24). For instance, examinations of growth patterns among British children were conducted by the Expert Group on Growth Standards of the Scientific Advisory Group on Nutrition and Royal College of Paediatrics and Child Health (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The finding we report here indicated only a slightly higher prevalence of child stunting compared to the previous study, perhaps because of the use of the new WHO reference group. When the new WHO 2006 references are used, rather than the NCHS and CDC charts/references, it leads to a higher proportion of child stunting at all age groups (Schwarz et al, 2008) due to the fact that the WHO standards were developed more recently and with an multi-country, multi-ethnic, breast-fed, healthy cohort across different countries (de Onis et al, 2004; Borghi et al, 2006). …”
Section: Discussionmentioning
confidence: 99%